A Novel Competitive Binding Screening Assay Reveals Sennoside B as a Potent Natural Product Inhibitor of TNF-alpha - Peng, Lei; Durai, Prasannavenkatesh; Park, Keunwan; Pyo, Jeong Joo; Choi, Yongsoo (MDPI, 2021)
Natural products (NPs) have played a significant role in drug discovery for diverse diseases, and numerous attempts have been made to discover promising NP inhibitors of tumor necrosis factor alpha (TNF-alpha), a major therapeutic target in autoimmune diseases. However, NP inhibitors of TNF-alpha, which have the potential to be developed as new drugs, have not been reported for over a decade. To facilitate the search for new promising inhibitors of TNF-alpha, we developed an efficient competitive binding screening assay based on analytical size exclusion chromatography coupled with liquid chromatography-tandem mass spectrometry. Application of this screening method to the NP library led to the discovery of a potent inhibitor of TNF-alpha, sennoside B, with an IC50 value of 0.32 mu M in TNF-alpha induced HeLa cell toxicity assays. Surprisingly, the potency of sennoside B was 5.7-fold higher than that of the synthetic TNF-alpha inhibitor SPD304. Molecular docking was performed to determine the binding mode of sennoside B to TNF-alpha. In conclusion, we successfully developed a novel competition binding screening method to discover small molecule TNF-alpha inhibitors and identified the natural compound sennoside B as having exceptional potency.